ECONOMIC SIGNIFICANCE OF "DEROCERAS RETICULATUM MULLER" AND "1774 CANDAHARIA LEVANDERI SIMROTH, 1901" SPECIES - Abdulazizova Shoira Karimovna; Norkobilova Ugiloy Kholmumin Kizi; Abdulloeva Dilnoza Boboismoilovna; Rashidova Gurdofarid Erkinovna; Kayimova Nodira Ravshan Kizi (American Journal Of Agriculture And Horticulture Innovations, 2023)
The article provides information about the economic importance of the species "Deroceras reticulatum Muller" and "1774 Candaharia levanderi Simroth, 1901" found in the village of Machai, Boysun district.